Novel Methods for Assessing Oral Direct Factor Xa and Thrombin Inhibitors: Use of Point-of-Care Testing and Urine Samples - Harenberg, Job; Du, Shanshan; Krämer, Sandra; Giese, Christina; Schulze, Astrid; Weiss, Christel; Krämer, Roland (Seminars in Thrombosis and Hemostasis, 2013)
Rivaroxaban and dabigatran are new oral anticoagulants (NOACs) that inhibit directly factor Xa and thrombin, respectively. These NOACs effectively prevent thromboembolic complications using fixed doses without the need for dose adjustment according to laboratory results. About 60% of rivaroxaban is cleared from circulation by glomerular filtration, 30% of which is excreted as active drug. About 80% of dabigatran is excreted into urine as active compound. Accordingly, both NOACs can be determined in urine by means of chromatographic methods. Only a few laboratories are able to perform such methods, and results are not available within short time frames. New methods have to be developed to obtain results within minutes and possibly as point-of-care (POC) techniques. This testing may be useful for special patient populations such as those with acute deterioration of renal function due to any disease, before surgical interventions, during unexpected bleeding or thrombotic episodes while on therapy with NOACs, the oldest and youngest populations, pregnancy, suspicion of overdose and intoxication, and to determine adherence to therapy. Here we describe results of a POC qualitative assay using urine samples from patients on treatment with dabigatran and rivaroxaban.
Keywords: new oral anticoagulants; dabigatran; rivaroxaban; point-of-care method; urine